In situ X‐ray diffraction study of point defects in neptunium dioxide at elevated temperature. (1st June 2014) - Chollet, M.; Léchelle, J.; Belin, R. C.; Richaud, J.‐C.
<x xml:space="preserve">Abstract</x> High‐temperature X‐ray diffraction measurements have been performed on neptunium dioxide up to 2000 K for the first time under He, He/5%H2 and air atmospheres. Up to 1643 K, NpO2 remains stoichiometric under all the considered atmospheres, and the coefficients of thermal expansion have been evaluated. Above 1643 K, the lattice parameter departs from linearity towards higher values. The atomic displacement parameters of the O and Np atoms were determined from Rietveld refinement and the Debye temperature subsequently obtained. This was used to study the contribution of point defects to the evolution of the lattice parameter at elevated temperature by estimating the energy of formation of vacancies. It is shown that only the chemical reduction of NpO2 to NpO2−x is responsible for the departure from linearity below 1750 K. Above this temperature, the evolution is due to the simultaneous effect of reduction and the formation of oxygen Frenkel pairs.